The Writerpreneur E-Platform Based on a Metacognitive Approach in Improving Essay Writing Competence and Digital Literacy Entrepreneurship - Raden Ika Mustika; Reka Yuda Mahardika; Dede Endang Mascita; Emi Kulsum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The problem of this research lies in the suboptimal utilization of students' writing skills in the field of digital literacy entrepreneurship and the still low self-regulation and metacognitive abilities in the essay writing process. Writing learning in higher education still focuses on the final result, so that the process of planning, monitoring, and evaluation of writing has not been developed optimally. This study aims to analyze, evaluate, and test the effectiveness of the writerpreneur e-platform based on a metacognitive approach in improving students' essay writing and digital literacy entrepreneurship competencies. This study used a quasi-experimental research type with a nonequivalent control group design. The research subjects were 250 students and who were divided into experimental and control groups of 125 students each. Data collection methods were carried out through essay writing tests, digital entrepreneurship questionnaires, observations, and interviews using writing assessment rubrics, Likert scales, and interview guidelines. Data analysis used descriptive statistics, ANCOVA, chi-square tests, and t-tests. The results of the study indicate that the metacognitive-based writerpreneur e-platform significantly improves essay writing competency in the aspects of task achievement, coherence and cohesion, vocabulary, and grammatical accuracy, while also increasing students' motivation, interest, attitude, and self-efficacy in digital literacy entrepreneurship. The conclusion of the study shows that the integration of metacognitive-based technology effectively optimizes students' writing and digital entrepreneurship skills.